2011
DOI: 10.5194/acpd-11-29479-2011
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The climatology, propagation and excitation of ultra-fast Kelvin waves as observed by meteor radar, Aura MLS, TRMM and in the Kyushu-GCM

Abstract: Wind measurements from a meteor radar on Ascension Island (8° S, 14° W) and simultaneous temperature measurements from the Aura MLS instrument are used to characterise ultra-fast Kelvin waves (UFKW) of zonal wavenumber 1 (E1) in the mesosphere and lower thermosphere (MLT) in the years 2005–2010. These observations are compared with some predictions of the Kyushu-general circulation model. Good agreement is found between observations of the UFKW in the winds and temperatures, and also with the properties of the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…This allows us to determine both the period and zonal wave number of a fast travelling planetary wave using only a few days of data. Observations show that the two‐, three‐, and six‐day waves have a lifetime lasting over days to weeks (e.g., Davis et al, ; Pancheva et al, ; Tunbridge et al, ). An 11‐day running window stepped by one day at a time is thus sufficient to resolve the features of interest.…”
Section: Data and Analysis Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This allows us to determine both the period and zonal wave number of a fast travelling planetary wave using only a few days of data. Observations show that the two‐, three‐, and six‐day waves have a lifetime lasting over days to weeks (e.g., Davis et al, ; Pancheva et al, ; Tunbridge et al, ). An 11‐day running window stepped by one day at a time is thus sufficient to resolve the features of interest.…”
Section: Data and Analysis Methodsmentioning
confidence: 99%
“…Many observations have revealed the presence of fast travelling planetary waves with short periods (≤6 days) in the equatorial mesosphere and lower thermosphere (MLT; e.g., Garcia et al, ; Pancheva et al, , , ; Takahashi et al, ; Tunbridge et al, ; Davis et al, ; England et al, ; Gu et al, ; Liu et al, ). These include the westward propagating Rossby‐gravity waves (with periods approximately two days), and eastward propagating ultrafast Kelvin (with periods approximately three days), and fast Kelvin waves (with periods approximately six days).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A detailed study of the identification of this wave is reported by England et al [2012]. The month of January 2010 coincides with the onset of the SSW, but this wave occurs before the SSW and the 3-day wave often occurs in January [e.g., Vincent, 1993;Yoshida et al, 1999;Davis et al, 2011]. It is thus believed that this wave is not related to the SSW.…”
Section: Introductionmentioning
confidence: 99%